State and religion in Israel : a philosophical-legal inquiry - Sapir, Gideon (Cambridge University Press, 2018)
"State and Religion in Israel begins with a philosophical analysis of the two main questions regarding the role of religion in liberal states: should such states institute a 'Wall of Separation' between state and religion? Should they offer religious practices and religious communities special protection?"--